Thermoelectric device for fastening parts by freezing during machining - O. V. Evdulov; D. V. Evdulov; S. G. Gasanova; Z. M.–Z. Badrudinova (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of the study is to develop the design of a thermoelectric device for fastening parts by freezing during machining, and to analyze its parameters and characteristics.Method. The design of a thermoelectric device for fastening parts using the freezing method during their machining is described. The device includes a high-current fuel cell, made on the basis of layered thermoelements with improved thermomechanical characteristics. The fuel cell is interfaced with a heat-equalizing ceramic plate on the side of the cold junctions, and on the side of the hot junctions, through a similar ceramic plate, it is in contact with the heat release system.Result. To ensure the required operating mode of the device, a layered thermoelectric battery developed at the Research Institute of Semiconductor Thermoelectric Devices and Devices can be used in its composition. T.A. Ismailov”, Dagestan State Technical University.Conclusion. The operating power range of the used fuel cell is in the range of 20-50 W with an average temperature difference between the junctions of 50 K, the supply current is 50-80 A with a power consumption of 50-160 W. The refrigeration coefficient varies from 0.1 to 0.45.